Shrinkage character in the process of semi-coke formation - Guojie Zhang" (Science Faculty of Chiang Mai University, 2019)
A mini coke oven has been used to study the shrinkage crack character in the process of semi-coke formation. The results show that the section of coke cake has been clearly layered, from the inner to outward, divided into loose honeycomb semi-coke layer, small honeycomb semi-coke layer, compact semi-coke layer, cracks layer. The colour of loose honeycomb semi-coke layer and small honeycomb semi-coke layer is dark black, and its porosity about 44.8%. The colour of the compact semi-coke layer is bright black, and its porosity about 34.0%. The colour of cracks layer is silver gray, and its porosity about 46.0%. The pyrolytic plastic layer area of static and dynamics state difference, the static state pyrolytic plastic layer area is an obturation flat elliptic area, wrapped in the middle of semi-coke; the dynamic state pyrolytic plastic layer area is a placket oblate gasbag, wrapped by semi-coke from the outside. The shrinkage rate of semi-coke increases with temperature increase, the relationship between shrinkage and temperature can be described as Y=-7 X2×10-5+0.14X-56.26 (600℃-850℃). The thickness of semi-coke decreases, with increasing temperature, crack increases and clump decreases. Add proper humidity to coal, the crack of semi-coke decreases and the clump increases.